Über ganzzahlige Darstellungen der zyklischen Gruppe von vierter Ordnung - Matuliauskas, A. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Матуляускас, О целочисленных представлениях циклической группы четвертого порядка A. Matuliauskas, Apie 4-os eilės ciklinės grupės sveikaskaičius atvaizdavimus